1956
DOI: 10.1121/1.1908216
|View full text |Cite|
|
Sign up to set email alerts
|

Tabular Data of the Velocity and Absorption of High-Frequency Sound in Mammalian Tissues

Abstract: This report is a condensed presentation of currently available data on the velocity and absorption of high-frequency sound in mammalian tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
4

Year Published

1957
1957
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(33 citation statements)
references
References 0 publications
0
29
0
4
Order By: Relevance
“…The range for the speed of sound in the entire temporal bone was also reported to be from 2570 to 3030 m/s by Fry and Barger (1978). Goldman and Hueter (1955) and Goss et al (1978) reported a speed of sound in skull of 3360 m/s at 0.8 MHz. Three of our skulls exhibited a speed of sound in the range found in the literature.…”
Section: Discussionmentioning
confidence: 94%
“…The range for the speed of sound in the entire temporal bone was also reported to be from 2570 to 3030 m/s by Fry and Barger (1978). Goldman and Hueter (1955) and Goss et al (1978) reported a speed of sound in skull of 3360 m/s at 0.8 MHz. Three of our skulls exhibited a speed of sound in the range found in the literature.…”
Section: Discussionmentioning
confidence: 94%
“…The diameter of the ultrasonic beam was 2.5 mm. The data were compiled from ICRU (1998), Hueter (1952), Hill et al (2004), Goldman and Hueter (1956) and Nahirnyak et al (2006). Experimental results for the maximum temperature rise measured in tissue exposed to pulsed ultrasound (PRP = 10 ms, P p-t-p = 0.25 MPa, I SPTA = 0.4 W/cm 2 , T = 37 °C, t = 300 s) in vitro …”
Section: Discussionmentioning
confidence: 99%
“…The values for frequency-dependent absorption coefficients utilized for the numerical calculations are presented in Table 1 (ICRU report 1998; Coussios et al 2002;Hueter 1952;Hill et al 2004;Goldman and Hueter 1956).…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Ekokardiyografi ile ventrikül duvarının hareketleri ve boşluğu, kalp kası büyümeleri ve kalp kapakları incelenebilmektedir. Yapılması basittir, fakat değerlendirilmesini yapabilmek için tecrübe sahibi olmak gerekir (3)(4)(5)(6)(7)(8).…”
Section: Ekokardiografinin Fiziğiunclassified